NOWE OBLICZE KONKURENCYJNOŚCI - KONSEKWENCJE DLA POLSKIEGO SEKTORA ŻYWNOŚCIOWEGO - Słodowa-Hełpa, Małgorzata (Wydział Prawa i Administracji UAM, 2003)
The article presents the process o f competitiveness development in a broad perspective and attempts to present the main factors determining its contemporary character. Additionally, the main instruments stimulating the competitiveness o f the Polish food industry are presented against this background. In particular, the challanges and requirements connected with the EU integration are emphasised. The development o f competitiveness is depicted in this context, both in national and regional development programmes, and an attempt is made to identify the basic elements that ensure the development of competitiveness in the agricultural and food industries as well as their technological and economic position. Among the main factors affecting competitiveness special emphasis is put on the role of quality, innovation, regional and local production systems, as well as horizontal and vertical integration processes.
NEW FACE OF COMPETITIVENESS - CONSEQUENCES FOR POLISH FOOD INDUSTRY